Water Temperature Monitoring System In IoT Based Freshwater Fish Farms - Muhammad Fahriansyah; Relita Buaton; Milli Alfhi Syari, (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
This research develops an Internet of Things (IoT)-based water quality monitoring system for freshwater fish farming that integrates several key sensors: DS18B20 for temperature measurement, turbidity sensor for water turbidity measurement, and ultrasonic sensor for water level monitoring. The system is equipped with two automatically controlled water pumps to maintain optimal conditions in the fish pond. The system works by reading water quality parameters in real-time using these sensors, then sending the data to the IoT platform via a WiFi network. The data is processed by an ESP32 microcontroller that will automatically activate the water pump when it detects a parameter change that exceeds a specified threshold and provides notifications to the farmer via a mobile application. Test results show that this system is able to automatically monitor water temperature and turbidity levels in pond water based on the temperature and turbidity data obtained